Gut Microbiota Alterations Associated with Viral Activity in Chronic Hepatitis B - Nasta, Paola; Di Gregorio, Marco; Zaia, Monica; Carosi, Giampiero (Archives of Case Reports, 2026)
Background: The gut–liver axis plays a pivotal role in chronic liver diseases, and increasing evidence links gut microbiota dysbiosis to disease progression in chronic hepatitis B (CHB). However, data comparing microbiota features between patients with active and inactive HBV infection remain limited. Methods: We performed a retrospective analysis of gut microbiota composition and functional potential in patients with chronic HBV infection, stratified according to viral activity as defined by current EASL guidelines. Microbial diversity, taxonomic composition, enterotypes, pathobiont prevalence, and predicted metabolic pathways were compared between active and inactive HBV infection. Results: Patients with active HBV infection exhibited significantly reduced microbial α-diversity, lower phylogenetic diversity, and decreased evenness compared with inactive carriers, despite virological suppression under antiviral therapy. Active HBV was associated with Prevotella-dominated enterotypes, expansion of pathobionts (Escherichia coli, Klebsiella pneumoniae, Bacteroides fragilis), and depletion of beneficial symbionts, particularly short-chain fatty acid– and indole-producing taxa, including Faecalibacterium prausnitzii, Roseburia intestinalis, Blautia wexlerae, and Alistipes spp. Functional profiling revealed reduced production of butyrate, propionate, acetate, and indole derivatives, alongside increased synthesis of ethanol, secondary bile acids, and lipopolysaccharides. Conclusion: Active CHB is characterized by a distinct dysbiotic and pro-inflammatory gut microbiota profile that persists despite effective antiviral therapy. These findings support a contributory role of gut microbiota in immune dysregulation and disease activity in CHB and provide a rationale for microbiota-targeted interventions as complementary therapeutic strategies.